2007
DOI: 10.1037/0022-0663.99.3.626
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monological and dialogical argumentation on concept learning in evolutionary theory.

Abstract: In this study the effects of argumentation-eliciting interventions on conceptual understanding in evolution were investigated. Two experiments were conducted: In the first, 76 undergraduates were randomly assigned to dyads to collaboratively solve and answer items in evolution; half of them were instructed to conduct an argumentative discussion, whereas control dyads were only asked to collaborate. In the second experiment, 42 singletons participated in one of two conditions: Experimental students engaged in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 60 publications
11
124
0
11
Order By: Relevance
“…There are significant differences between pre and post test for the experimental group in both argument (1) and argument (2). This result indicates the impact of implementing the suggested strategy "QCEJ" in developing constructing scientific arguments skills.…”
Section: Pre-and Post-test For Experimental Group Argument (1) and (2)supporting
confidence: 50%
See 1 more Smart Citation
“…There are significant differences between pre and post test for the experimental group in both argument (1) and argument (2). This result indicates the impact of implementing the suggested strategy "QCEJ" in developing constructing scientific arguments skills.…”
Section: Pre-and Post-test For Experimental Group Argument (1) and (2)supporting
confidence: 50%
“…The Pearson Correlation is carried out to show the correlations between the examined variables of argument (1) and (2). The three argument construction skills: claim, evidence, and justification correlate positively with each other in both arguments.…”
Section: Relationship Between Skills Of Argument (1) and Argument (2)mentioning
confidence: 99%
“…This approach allows students to engage in authentic, but appropriately scaled, practices of scientific communication and reasoning. Moreover, consensus-building through argumentation has the potential to support knowledge construction for individual students as they learn to draw upon and synthesize evidence in order to build stronger arguments (e.g., Asterhan & Schwarz, 2007; 2009; Kuhn, 2010;Kuhn, Shaw, & Felton, 1997;Limón & Carretero, 1997;Sampson & Clark, 2009;Schwarz, Neuman, & Biezuner, 2000). In fact, as seen in Table 1, nearly all groups that began with dissention moved towards consensus around the correct claim, while discussing the key concept for the activity: competition between species.…”
Section: Instructional Implicationsmentioning
confidence: 99%
“…In fact, studies of whether and how argumentation affects an individual's understanding consistently show that becoming aware of challenges and counterarguments is beneficial to students. By confronting counter-arguments, students improve the structure and completeness of their own arguments (e.g., Kuhn, 2010;Kuhn, Shaw, & Felton, 1997;Limón & Carretero, 1997) and improve their understanding of the content under study (Asterhan & Schwarz, 2007;Sampson & Clark, 2009;Schwarz, Neuman, & Biezuner, 2000). For example, in a study of 10 th graders studying genetics, Venville and Dawson (2010) found that students that engaged in a brief argumentative intervention developed stronger arguments and deeper understandings of the science content than did those students without the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is scarce research testing these benefits, some empirical evidence on peer interactions partially supports it (Asterhan & Schwarz, 2007Howe et al, 2007). Some studies have tested the effect of the argumentative type of whole-class talk on learning, but they are only partially conclusive and do not prove the effect of the discussion of contradictory ideas (Che & She, 2012;Mercer, Dawes, Wegerif, & Sams, 2004;Venville & Dawson, 2010;Wilson, Taylor, Kowalski, & Carlson, 2010;Zohar & Nemet, 2002).…”
mentioning
confidence: 99%